Irregularities in Bundling and Tying Practices Home Loans and Insurance - Nowak, Katarzyna (Journal of Finance and Financial Law, 2022)
Banks, as part of cooperation with insurance companies, offer customers insurances. The of insurance is securing loan repayment. Polish Financial Supervision Authority (KNF) issued a number of reports on this subject. Identified by KNF numerous irregularities and the previous nonregulation resulted in 2014 r. publish Recommendation U. After the Recommendation U the national legislator as a result of the implementation of the directives introduced many significant changes in the area of bancassurance, which fundamentally changed the way banks offer insurance and strengthened the position of consumers. The idea of offering home loans with insurance is currently being realized as part of bundling and in certain situations also in tying practices and the position of the consumer is strengthened for example by information obligations imposed on banks. The main purpose of the article is to present the definition of the concept, forms and the scope of its application by the search banks, causes and consequences of improper bundling and tying practices and to indicate repair solutions. The presented objective of the project fits in with the research gap in the literature on the subject. Currently, there are no studies that would analyze the consequences for consumers of bundling and tying practices insurance with a home loan. Methodology. In theoretical part of the article author used analysis of the literature and a review of legal regularions. In order to determine the nature of irregularities occurring in the process of offering insurance by banks author used analysis how banks offers mortgage credit with insurance. Author also used in the article several examples of complains submitted by consumer to Financial Ombudsman in the years 2017–2021. The result of the research. The research allowed to notice current irregularities that may indicate a violation of consumer interests on the bancassurance. The identified irregularities are occuring for example in offering insurance that is unsuited to the client’s needs, misleading or concluding a contract basing only verbal information. The mismatch of loan repayment insurance is largely due to deficiencies in the credit process.